Scale-Up Preparation and Characterization of Collagen/Sodium Alginate Blend Films - Zhe Wang; Shuaifeng Hu; Huaiyu Wang (Journal of Food Quality)
In an effort to produce scale-up of edible films, collagen-based films including different amounts of sodium alginate (CS) were prepared by casting method. Films were characterized based on their rheological, thermal, and mechanical properties, water vapor permeability (WVP), and oxygen permeability (OP). The microstructures were also evaluated by scanning electron microscopy (SEM), atomic force microscopy (AFM), and Fourier transform-infrared spectroscopy (FTIR). Furthermore, the addition of sodium alginate effectively improved the viscosity and thermal stability, significantly increased TS, and decreased E and WVP (P<0.05), but with no obvious effect on OP (P>0.05). SEM and AFM showed homogeneous matrix, with no signs of phase separation in the blends. Overall, films (CS2) produced using collagen (g) : sodium alginate (g) = 10 : 2 showed suitable rheological property (apparent viscosity was 4.87 m Pa s−1) and better TS (26.49 Mpa), E (64.98%), WVP (1.79 × 10−10 g·cm−1·s−1·Pa−1), and OP (3.77 × 10−5 cm3·m−2·d−1·Pa−1).